A New Technique for Simple Renal Cyst: Cystoretroperitoneal Shunt. (30th June 2009) - Canguven, Onder; Goktas, Cemal; Yencilek, Faruk; Cetinel, Cihangir; Albayrak, Selami
Abstract : Purpose . To evaluate the results of patient symptoms and radiologic outcomes of cystoretroperitoneal shunt (CRS) technique in the treatment of symptomatic simple renal cysts. Patients and Methods . In a prospective study, 37 patients with a simple renal cyst were treated with ultrasound-guided percutaneous CRS-catheter. Radiological success was indicated as no recurrence of the cyst or a reduction in cyst volume by at least half. Results . CRS technique was performed successfully in 36 patients with a simple renal cyst. The mean size of all cysts decreased from 8.8 cm (range 7 to 14) to 1.7 cm (range 0 to 9;P < .001 ). Symptomatic success (pain relief) was achieved in 29/36 (80.5%) of patients, and radiographic success was achieved in 23/36 (63.8%) of patients, with a median follow-up of 16 months (range 6 to 24). Conclusion . Ultrasound-guided percutaneous CRS technique for simple renal cysts is fast, safe, effective, and inexpensive.